Design Matching and Dynamic Performance Test for an HST-Based Drive System of a Hillside Crawler Tractor - Zhijie Liu; Guoqiang Zhang; Guoping Chu; Hanlin Niu; Yazhou Zhang; Fuzeng Yang (Agriculture, 2021)
In recent years, research into and development of hillside tractors has become a popular topic in the field of agricultural engineering in China. To solve the main problems associated with a low adjustment range of the working speed, complex operation, and low safety for slope operation of medium-sized crawler tractors, a hydrostatic drive system that can be used for hillside crawler tractors was designed. According to the operation requirements of a hillside crawler tractor, the parameters of the three-cylinder diesel engine, hydrostatic transmission (HST), drive rear axle, and other key components of the drive system were matched after the force and motion analyses of the tractor, and then the main performance indicators, including the traction performance, system pressure and working speed of the drive system were verified. On this basis, a drive system performance test bench was built, and the traction performance and starting acceleration performance of the drive system was tested. The results of the traction bench test show that when the engine was at the maximum torque point of 1700 r/min, the maximum theoretical tractive force outputted by the tractor in Gear I was 114,563 N, and the maximum theoretical tractive force outputted by tractor in Gear II was 10,959.2 N, which were both larger than the traction resistance of 9550.6 N experienced by the hillside tractor ploughing on the slope. The results of the initial acceleration bench test show that the tractor driving speed can gradually increase with increasing output of the variable pump and can reach the maximum in 3 s. When the tractor was driving on flat ground, the maximum driving speeds of Gear I, Gear II, and Gear III were 4.65 km/h, 6.58 km/h, and 8.57 km/h, respectively, which are close to the theoretical values. When the tractor was driving on a 15° slope, the maximum driving speeds of Gear I, Gear II, and Gear III were 4.55 km/h, 6.25 km/h, and 8.28 km/h, respectively. It can be concluded that the design matching of the drive system is reasonable, the speed consistency is good and there is enough power reserve, which can meet the requirements for a large workload.